Development Of Ionic Liquid As Catalyst For Transesterification Reaction - Alimuddin, Jamila Binti; Yarmo, Prof.Dr. Mohd Ambar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Maritim Raja Ali Haji, 2013)
Ionic liquid had a various uses and among them is as catalyst in a reaction. This research was carried out to synthesis and developed the choline chloride based ionic liquid to investigate their ability as a catalyst in transesterification reaction. The ionic liquid synthesized was choline chloride.2ZnCl2 and choline.2urea based system. Both of the ionic liquid synthesize were characterized by using Infra-red spectroscopy (FTIR) and Nuclear Magnetic Resonance spectroscopy (1H NMR & 13C NMR). Characterization result confirmed the functional group and the structure of the ionic liquids was as expected. Both ionic liquid were applied as a catalyst for the transesterification reaction and the resulting product was analyzed by GC-FID and GCxGC-MS (ToF). The transesterification reaction of palm olein and buthanol with the presence of choline chloride.2ZnCl2 gives 25.7% yields while with the use of choline chloride.2urea gives 25.0% yields. The results show that the acidity of choline chloride.2ZnCl2 and the basic properties of the choline chloride.2urea were not really suitable to be used as catalyst in the transesterification reaction.